Pengaruh Cita Rasa Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Warung Makan Soto Betawi - Elsa Anggraeni Piliyanto; Hadita Hadita (Universitas 45 Surabaya, 2023)
The purpose of this study was to ascertain the variables that typically have an effect on customer satisfaction at Soto Betawi Food Warungs as well as the relationship between taste and service quality and customer satisfaction at Soto Betawi Food Stalls. This study is quantitative in nature. The purposive location method is utilized in this research strategy. The accidental sampling method of 71 respondents is used to determine the number of respondents using the Non Propability Sampling method. Questionnaires, observation, and data processing techniques like editing, scoring, and tabulation are used to gather information. The information examination utilized is inferential/measurable investigation including various straight relapse line examination, relapse line change investigation, F test, different coefficient of assurance, T test, viability of relapse lines, and standard blunders of assessments. At Warung Makan Soto Betawi, the findings indicate that both the variables of taste and service quality have a significant impact on customer satisfaction.